Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

Алгебра 8 класс Ю.Н.Макарычев, Н.Г.Миндюк, К.И.Нешков, С.Б.Суворова

авторы: , , , .
издательство: "Просвещение" 2013 г

Раздел:

Номер №38

Упростите выражение:
а)
$\frac{a - b}{b - a}$
;
б)
$\frac{(a - b)^2}{(b - a)^2}$
;
в)
$\frac{(a - b)^2}{b - a}$
;
г)
$\frac{a - b}{(b - a)^2}$
;
д)
$\frac{(-a - b)^2}{a + b}$
;
е)
$\frac{(a + b)^2}{(-a - b)^2}$
.

Решение а

$\frac{a - b}{b - a} = \frac{a - b}{-(a - b)} = -1$

Решение б

$\frac{(a - b)^2}{(b - a)^2} = \frac{(a - b)^2}{(a - b)^2} = 1$

Решение в

$\frac{(a - b)^2}{b - a} = \frac{(b - a)^2}{b - a} = b - a$

Решение г

$\frac{a - b}{(b - a)^2} = \frac{a - b}{(a - b)^2} = \frac{1}{a - b}$

Решение д

$\frac{(-a - b)^2}{a + b} = \frac{(a + b)^2}{a + b} = a + b$

Решение е

$\frac{(a + b)^2}{(-a - b)^2} = \frac{(a + b)^2}{(a + b)^2} = 1$